Evalusi Kelayakan Usaha Penggemukan Sapi Potong - Devionata Octaviananda; Titi Rapini (Universitas Muhammadiyah Ponorogo, 2020)
This study uses the theme of evaluating business feasibility. Where the object of the research is Mr. Katno's Beef Cattle Ranch located in the village of Tajug, Siman Ponorogo sub-district. This farm has been established since 1995 and still survives until now, so that evaluation needs to be done in this effort. In this study to determine whether the business is feasible or not by using an assessment of market aspects, technical aspects, management aspects, legal aspects, environmental aspects and financial aspects (NPV and IRR). Researchers use primary data in processing the data where the data comes from interviews with informants as owners, and secondary data from data that already exists on the internet, websites and government publications. The data analysis method uses qualitative and quantitative data analysis. The results of the study indicate that market aspects, technical aspects, management aspects, legal aspects, and environmental aspects have been concluded that can meet eligibility. Likewise, financial aspects, where the NPV was obtained at 466,261,640, IRR of 63.33% COC. Based on the results of the analysis of the research, the Beef Cattle Farming business owned by Mr. Katno is feasible to be implemented.